RESPON PERTUMBUHAN BIBIT TANAMAN GAHARU (Aquilaria malacensis) TERHADAP PEMBERIAN PUPUK PELENGKAP CAIR (PPC) ORGANIK - Linda Sisri Yenti; Adiwirman ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this study was to determine the effect of the concentration of organic PPC plant hormones lead to the growth of seedlings of aloes and searching for the best concentration for the growth of seedlings of aloes. This research has been led in the Plant Laboratory, Faculty of Agriculture, University of Riau, Pekanbaru. This study was conducted over four months from May 2015 until the month of August 2015.This study was conducted experiments using completely randomized design (CRD), which consists of 4 treatments ie: without granting PPC organic (P0), the concentration of PPC organic 1 ml / liter of water (P1), concentration PPC organic 2 ml / liter of water (P2) and the concentration of organic PPC 3 ml / liter of water (P3). In this study there were 4 treatments consists of three replicates so that there are 12 experimental units. Each unit contained three seedlings are planted in polybags and two seedlings were sampled.The parameters measured were plant height (cm), number of leaves (pieces), stem diameter (cm), large whole leaf per plant (cm2), fresh weight canopy (g), the weight of wet roots (gram), heavy wet leaves ( gram), shoot dry weight (grams), root dry weight (grams), leaf dry weight (grams). The significant difference (HSD) at 5% was used for mean separations. Based on the research granting PPC organic against aloes seeds can be concluded that the concentration PPC organic 2 ml / l of water showed the highest growth in the number of leaves, stem diameter, leaf area per plant, the weight of the wet canopy, wet weight root, fresh weight of leaves, dry weight canopy, root dry weight and leaf dry weight aloes seeds than other treatments, but the treatment of PPC at each concentration effect no significant effect on plant height. Keywords : seed aloes, growth, PPC organic